Learning styles and the prospective ophthalmologist. (April 2015) - Modi, Neil; Williams, Olayinka; Swampillai, Andrew J.; Waqar, Salman; Park, Jonathan; Kersey, Thomas L.; Sleep, Tamsin
Abstract: Purpose : Understanding the learning styles of individual trainees may enable trainers to tailor an educational program and optimise learning. Surgical trainees have previously been shown to demonstrate a tendency towards particular learning styles. We seek to clarify the relationship between learning style and learned surgical performance using a simulator, prior to surgical training. Methods : The Kolb Learning Style Inventory was administered to a group of thirty junior doctors. Participants were then asked to perform a series of tasks using the EyeSi virtual reality cataract surgery simulator (VR Magic, Mannheim, Germany). All completed a standard introductory programme to eliminate learning curve. They then undertook four attempts of level 4 forceps module binocularly. Total score, odometer movement (mm), corneal area injured (mm 2 ), lens area injured (mm 2 ) and total time taken (seconds) recorded. Results : Mean age was 31.6 years. No significant correlation was found between any learning style and any variable on the EyeSi cataract surgery simulator. Conclusion : There is a predominant learning style amongst surgical residents. There is however no demonstrable learning style that results in a better (or worse) performance on the EyeSi surgery simulator and hence in learning and performing cataract surgery.